PROPORTIONATE MAIMING: THE ORIGINS OF THOMAS JEFFERSON'S PROVISIONS FOR FACIAL DISFIGUREMENT IN BILL 64. (December 2019) - Cock, Emily
ABSTRACT: In 1779, Thomas Jefferson proposed the use of nose-cutting to punish women convicted of specific offences, and the use of retaliation ( lex talionis ) for anyone who deliberately disfigured another person. These punishments were intended to replace the death penalty for these crimes, and as such formed part of Jefferson's attempt to rationalise the Virginian law code in line with eighteenth-century reform principles. Jefferson drew on British laws from the Anglo-Saxon period to the Coventry Act for his bill, but his proposals contrast strikingly with British movements away from corporal marking as punishment used against their own citizens. This article examines the origins and fates of equivalent crimes and punishments in the law codes Jefferson examined, and compares the legal and wider connotations of facial appearance and disfigurement that made these proposals coherent in Virginia when they had long ceased elsewhere. Tracing examples and discussion of these intersecting cases will greatly increase our understanding of Jefferson's proposals, and the relationships between facial difference, stigma and disability in eighteenth-century America. CRYNODEB: Ym 1779, cynigiodd Thomas Jefferson y dylid cosbi menywod a oedd yn euog o droseddau penodol drwy dorri eu trwynau, a defnyddio dial ( lex talionis ) ar gyfer unrhyw un a anffurfiodd berson arall yn fwriadol. Bwriad y cosbau hyn oedd disodli'r gosb eithaf ar gyfer y troseddau hyn, ac felly roeddent yn rhan o ymgais Jefferson i resymoli cod cyfreithiol Virginia yn unol ag egwyddorion diwygio'r ddeunawfed ganrif. Cynlluniodd Jefferson fesur ar sail cyfreithiau Prydeinig o'r cyfnod Eingl-Sacsonaidd hyd at Ddeddf Coventry, ond roedd ei gynigion yn cyferbynnu'n drawiadol â symudiadau Prydain oddi wrth gosbi ei dinasyddion yn gorfforol. Mae'r erthygl hon yn edrych ar darddiad a thynged troseddau a chosbau cyfatebol y cyfreithiau roedd Jefferson yn eu harchwilio. Mae'n cymharu'r arwyddocâd cyfreithiol ac ehangach o ymddangosiad y wyneb ac anffurfio'r wyneb, a olygodd bod y cynigion hyn yn rhesymegol yn Virginia pan oeddent wedi dod i ben mewn mannau eraill ers amser maith. Byddwn yn cynyddu'n dealltwriaeth o gynigion Jefferson wrth olrhain enghreifftiau a thrafod yr achosion croestoriadol hyn, a'r berthynas rhwng anffurfio'r wyneb, stigma, ac anabledd yn America yn y ddeunawfed ganrif.